The Effect Of Investment Knowledge, Motivation, Capital On Students' Investment Interest In The Capital Market (Case Study On Sharia Banking Students Of Stai Yapnas Jeneponto) - Nurul Fauzia Ishak; Asri Jaya; Muhammad Adil (International Journal of Economic Research and Financial Accounting, 2024)
The purpose of this study is to determine the influence of knowledge, motivation, and capital on students' interest in investing in the capital market in Islamic banking students of STAI Yapnas Jeneponto. The research sample is 55 respondents from the 2020 and 2021 batches. The type of research used is quantitative. The data source in data collection is primary data using questionnaires. The instrument of this research is the Likert scale method. Based on the results of research using the SPSS V 24 program, shows that investment knowledge and motivation have a positive influence on students' interest in investing in the capital market. The higher the investment knowledge and encouragement from within and around will increase students' interest in investing in the capital market. Meanwhile, capital has no influence on students' interest in investing in the capital market. The high and low capital to invest does not affect students' interest in investing.